The Basics of Basic Income - John A. Kay (Intereconomics, 2017)
Attempting to turn basic income into a realistic proposal involves the reintroduction of elements of the benefit system which are dependent on multiple contingencies and also on income and wealth. The outcome is a welfare system which resembles those that already exist.
Keywords: 330